Alternatives for airport management in Brazil: The case of the innovative management model of the Zona da Mata regional airport. Issue 4 (21st October 2019) - da Costa, Vitor Augusto Martins; Ribeiro, Danielle Carvalho
Abstract : Purpose: This paper aims to answer the following question: Is PPP a financially viable alternative for the management of regional airports in Brazil? Design/methodology/approach: The methodology is based on the case study of the innovative model of Zona da Mata Regional Airport management. It was used Value for Money as a method to compare this case with the conventional airport management alternative. Findings: It was observed that, when compared to the airport management alternative through contracting third parties, the public–private partnership (PPP) provided a reduction of almost 70% of public spending on the management of this infrastructure. Besides the financial advantage, other benefits of this PPP contract were also observed. Research limitations/implications: The analyses carried out in this study are not exhaustive and can be improved and remade as the life cycle of the PPP contract studied is progressed. Practical implications: It was concluded, from the results found, that PPP is an efficient alternative for the management of regional airports in Brazil, and the model can be replicated for similar airports. Originality/value: When analyzing the results of this innovative project of managing a regional airport through a PPP, this work made it possible to measure the positive impacts of this alternative and demonstrate the potential of the PPP as an alternative for the management of other regional airports in Brazil.